Implementasi Aplikasi Peminjaman Dan Pembayaran Angsuran Pada BPR Kabupaten Bandung - Cepi Setiawan; . Rinawati (STMIK Mardira Indonesia, Bandung, 2015)
This research aims to design a system that can handle data management system loans and installment payments with computer-based clients. To support the research conducted, the necessary steps carefully collecting data. The steps used to obtain data and information that support the implementation of this study is the observation and interviews, information systems needed constructed by using the method structured approach, namely with the Waterfall method computer program is structured to develop an information system with a database specifically to serve the needs of data management system of borrowing and repayment customers. Borrowing data management information system and computerized customer payments can facilitate the borrowing and payment data checking customers. As an initial step analysis to determine system requirements, and then implemented using the program Delphi 7 and Microsoft Access as a data processor borrowing and repayment. With the new system is able to solve the problems on the old system. Resulting in a system that can facilitate BPR Bandung Regency in performing data management installment. Keywords: borrowing and repayment; waterfall; delphi 7